2019
DOI: 10.3389/fped.2019.00364
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Pediatric Cerebral Venous Sinus Thrombosis: An Analysis of 30 Cases in China

Abstract: Background: Cerebral venous sinus thrombosis (CVST) in children is rare in a clinical setting. The aim of this study was to summarize the etiological, clinical, and imaging characteristics of CVST in children.Methods: We retrospectively analyzed the data of 30 patients with a diagnosis of CVST who were admitted to Children's Hospital of Fudan University from 2008 to 2018. The medical records, including clinical manifestations, laboratory data, neurological findings, treatment, and short-term prognosis were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 18 publications
2
29
2
Order By: Relevance
“…5,20 Reports have shown that 23% to 30% of patients with pediatric CVST are dehydrated. 4,5,11 A review described inherited thrombophilia (protein C, S, anti-thrombin III deficiencies, factor V Leiden mutation) in 20% to 62% and anti-phospholipid syndrome in 17% of patients having pediatric CVST. 3 Other common risk factors include chronic diseases that lead to a prothrombotic state such as systemic lupus erythematosus, nephrotic syndrome, nephritis, head trauma and malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,20 Reports have shown that 23% to 30% of patients with pediatric CVST are dehydrated. 4,5,11 A review described inherited thrombophilia (protein C, S, anti-thrombin III deficiencies, factor V Leiden mutation) in 20% to 62% and anti-phospholipid syndrome in 17% of patients having pediatric CVST. 3 Other common risk factors include chronic diseases that lead to a prothrombotic state such as systemic lupus erythematosus, nephrotic syndrome, nephritis, head trauma and malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Dehydration which is often associated with infections in pediatric patients is also a risk factor for CVST. 5,20 Reports have shown that 23% to 30% of patients with pediatric CVST are dehydrated. 4,5,11…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the great variability in clinical manifestations and vague clinical symptoms, CSVT is extremely difficult to be diagnosed in children based on clinical manifestations alone, making it a relatively underrecognized condition 3,9 …”
Section: Discussionmentioning
confidence: 99%